1999
DOI: 10.1038/sj.ejcn.1600682
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and antioxidant effects of quercetin from onions, in man

Abstract: Objective: To investigate the in vivo effects of quercetin following the ingestion of fried onions. Design: Five healthy volunteers, three males and two females aged between 25 and 39 y, ingested 225 g of fried onions after an overnight fast and peripheral venous blood was collected 0, 2, 4, 24 and 48 h after consumption. Quercetin in the plasma, total antioxidant capacity and susceptibility of low density lipoproteins (LDL) to oxidation were measured. Results: Following the onion meal, quercetin levels increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(61 citation statements)
references
References 26 publications
(46 reference statements)
5
55
0
Order By: Relevance
“…In vivo the oxidation of LDL has been shown to be a mediating factor in atherosclerosis development (Aviram, 1983;Palinski et al, 1989;Steinberg et al 1989) and Fuhrman et al (1995) have reported a 20% reduction in the propensity of plasma to undergo oxidation following 2 weeks of supplementation with 400 ml red wineaday. Recently McAnlis et al, (1999) have shown that, although dietarȳ avonoids are extensively absorbed, they do not accumulate within the LDL but are tightly bound to plasma proteins located predominantly within the HDL fraction. In this state, no signi®cant protection can be afforded to LDL but¯avonoids or their metabolites may prevent the oxidation of plasma proteins or lipids located within the HDL fraction.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo the oxidation of LDL has been shown to be a mediating factor in atherosclerosis development (Aviram, 1983;Palinski et al, 1989;Steinberg et al 1989) and Fuhrman et al (1995) have reported a 20% reduction in the propensity of plasma to undergo oxidation following 2 weeks of supplementation with 400 ml red wineaday. Recently McAnlis et al, (1999) have shown that, although dietarȳ avonoids are extensively absorbed, they do not accumulate within the LDL but are tightly bound to plasma proteins located predominantly within the HDL fraction. In this state, no signi®cant protection can be afforded to LDL but¯avonoids or their metabolites may prevent the oxidation of plasma proteins or lipids located within the HDL fraction.…”
Section: Discussionmentioning
confidence: 99%
“…Most measure the inhibition of an arti®cially generated oxidative process in the plasma. Although they differ in choice of oxidation source, target and the type of measurement used to detect the oxidized product (Woodford & Whitehead, 1998), in general such methods have detected transient increases in plasma antioxidant capacity following consumption of polyphenol-rich preparations of green tea (Sera®ni et al 1996;Benzie et al 1999;Nakagawa et al 1999), red wine (Fuhrman et al 1995;Whitehead et al 1995;Duthie et al 1998), alcohol-free red wine (Sera®ni et al 1998), whisky (Duthie et al 1998), grape seeds (Koga et al 1999) and onions (McAnlis et al 1999). However, any changes in plasma antioxidant capacity after consumption of polyphenols does not necessarily imply with certainty that analogous changes in redox status occur within relevant cells and tissue.…”
Section: Antioxidant Actionmentioning
confidence: 99%
“…Six carotenoids (a-carotene, b-carotene, b-cryptoxanthin, zeaxanthin, lycopene and lutein) are found in appreciable amounts in human serum (65,70) . Other candidate biomarkers of FV intake include antioxidant vitamins such as vitamin C (71,72) and flavonoids (73,74) , including quercetin (75) . Some of these compounds have been reliably associated with a particular fruit or vegetable, or a class of FV in observational studies, but less successfully with total FV consumption (69,70,72,(76)(77)(78)(79)(80) .…”
Section: Measuring Fruit and Vegetable Intakementioning
confidence: 99%